Utility of Cardiovascular Magnetic Resonance-Derived Wave Intensity Analysis As a Marker of Ventricular Function in Children with Heart Failure and Normal Ejection Fraction - Ntsinjana, Hopewell N.; Chung, Robin; Ciliberti, Paolo; Muthurangu, Vivek; Schievano, Silvia; Marek, Jan; Parker, Kim H.; Taylor, Andrew M.; Biglino, Giovanni (Frontiers in Pediatrics, 2017)
Objective This study sought to explore the diagnostic insight of cardiovascular magnetic resonance (CMR)-derived wave intensity analysis to better study systolic dysfunction in young patients with chronic diastolic dysfunction and preserved ejection fraction (EF), comparing it against other echocardiographic and CMR parameters. Background Evaluating systolic and diastolic dysfunctions in children is challenging, and a gold standard method is currently lacking. Methods Patients with presumed diastolic dysfunction [n = 18; nine aortic stenosis (AS), five hypertrophic, and four restrictive cardiomyopathies] were compared with age-matched control subjects (n = 18). All patients had no mitral or aortic incompetence, significant AS, or reduced systolic EF. E/A ratio, E/E′ ratio, deceleration time, and isovolumetric contraction time were assessed on echocardiography, and indexed left atrial volume (LAVi), acceleration time (AT), ejection time (ET), and wave intensity analyses were calculated from CMR. The latter was performed on CMR phase-contrast flow sequences, defining a ratio of the peaks of the early systolic forward compression wave (FCW) and the end-systolic forward expansion wave (FEW). Results Significant differences between patients and controls were seen in the E/E′ ratio (8.7 ± 4.0 vs. 5.1 ± 1.3, p = 0.001) and FCW/FEW ratio (2.5 ± 1.6 vs. 7.2 ± 4.2 × 10−5 m/s, p < 0.001), as well as—as expected—LAVi (80.7 ± 22.5 vs. 51.0 ± 10.9 mL/m2, p < 0.001). In particular, patients exhibited a lower FCW (2.5 ± 1.6 vs. 7.2 ± 4.2 × 10−5 m/s, p < 0.001) in the face of preserved EF (67 ± 11 vs. 69 ± 5%, p = 0.392), as well as longer isovolumetric contraction time (49 ± 7 vs. 34 ± 7 ms, p < 0.001) and ET/AT (0.35 ± 0.04 vs. 0.27 ± 0.04, p < 0.001). Conclusion This study shows that the wave intensity-derived ratio summarizing systolic and diastolic function could provide insight into ventricular function in children, on top of CMR and echocardiography, and it was here able to identify an element of ventricular dysfunction with preserved EF in a small group of young patients.